ANALISIS TINDAKAN AGRESI DALAM FILM ANIMASI DISNEY - Alyssa, Luthfia Nur; Fuady, Ikhsan; Wibowo, S. Kunto Adi (JIKE : Jurnal Ilmu Komunikasi Efek, 2022)
Film since decades ago has become one of the media consumed by many people to fulfill various needs, from education to entertainment. However, in reality there are many films that feature acts of aggression, one of which is animated films. This study aims to determine what acts of aggression are shown in Disney animated films, whether there are acts of physical, verbal, and indirect aggression, how often acts of physical, indirect, and verbal aggression are shown, what acts of aggression are most often shown, and whether there is a difference in the amount of physical, indirect, and verbal aggression in Disney animated films. This research was conducted using a quantitative approach and content analysis method. All scenes in the Disney animated film Tangled and Luca, totaling 100 scenes, were used as population and samples. Data collection is done by using a coding book. The data that had been coded were analyzed using descriptive statistics and comparatively using the Kruskal Wallis test. This study found that there were acts of physical, indirect, and verbal aggression in Disney animated films with indirect aggression in the form of dirty stares as the most displayed acts of aggression. In addition, this study also found that there was no significant difference in the amount of physical, indirect, and verbal aggressions in Disney animated films.